The Heart Block Hat-Trick: A Case of Alternating First-, Second-, and Third-Degree Heart Blocks - Nicholas Huerta; Salman Malik; Christopher Haas (Case Reports in Cardiology)
Idiopathic third-degree atrioventricular (AV) block in a relatively young patient is an uncommon phenomenon. Even more rare is when the third-degree heart block is alternating with the first- and second-degree AV blocks. In this case, we present a 39-year-old man with varying degrees of AV block, alternating the third-degree, second-degree, and first-degree AV blocks. The patient underwent an extensive workup for underlying etiologies, and results were inconclusive. A pacemaker was implanted and set for physiologic pacing via left bundle branch area pacing (LBBAP). This case will discuss potential genetic abnormalities associated with AV block and highlight LBBAP as an emerging technique for physiologic pacing.